2011
DOI: 10.1002/mus.21923
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of muscles affected by myositis using magnetic resonance elastography

Abstract: Introduction-Idiopathic inflammatory myopathies (IIM or myositis), is a group of autoimmune diseases that result in decreased muscle strength and/or endurance. Non-invasive tools to assess muscle may improve our understanding of the clinical and functional consequences of myopathies and their response to treatment. This study examined Magnetic Resonance Elastography (MRE), a non-invasive technique that assesses the shear modulus (stiffness) of muscle, in IIM subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 21 publications
(28 reference statements)
1
31
0
2
Order By: Relevance
“…On the basis of the results of this study, there is a need to define the normal strains of age-specific groups. Third, we did not confirm our findings by alternative methods, such as magnetic resonance elastography (McCullough et al 2011) or other strain measurement methods (Ma et al 2013). However, there is still no gold standard for the measurement of peripheral nerve strain both in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 63%
“…On the basis of the results of this study, there is a need to define the normal strains of age-specific groups. Third, we did not confirm our findings by alternative methods, such as magnetic resonance elastography (McCullough et al 2011) or other strain measurement methods (Ma et al 2013). However, there is still no gold standard for the measurement of peripheral nerve strain both in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 63%
“…Of note, a single study of nine patients with idiopathic inflammatory myopathy demonstrated a role for MR elastography in the detection of active myositis [30]. Future studies utilizing shear-wave elastography and MR elastography could demonstrate a role for elastography in the assessment of active myositis in children with JIIM.…”
Section: Discussionmentioning
confidence: 97%
“…Все элементы сократитель-ных и несократительных структур мышцы должны иметь вклад в скорость волны и ее поддержание в лю-бой точке мышцы. Эффект жировых отложений и ин-фильтрации существенно влияет на результаты, так же как наличие отека и воспаление мышцы [117]. Все это может привести к появлению проблем как при оценке результатов, так и при выполнении исследования.…”
Section: лекции и обзорыunclassified